2019
DOI: 10.1021/acs.biochem.9b00422
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of Cargo–Motor Linkage Tunes Myosin VI Motility and Response to Load

Abstract: We examine the effect of cargo−motor linkage stiffness on the mechanobiological properties of the molecular motor myosin VI. We use the programmability of DNA nanostructures to modulate cargo−motor linkage stiffness and combine it with high-precision optical trapping measurements to measure the effect of linkage stiffness on the motile properties of myosin VI. Our results reveal that a stiff cargo−motor linkage leads to shorter step sizes and load-induced anchoring of myosin VI, while a flexible linkage result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Hence, we propose that the release of myosin VI autoinhibition enhances motor flexibility and consequently the net flexibility of the motor-cargo linkage. In turn, the increased flexibility of the motor-cargo linkage has been previously shown to decrease the motor dwell time on the actin filament (tdwell) (32). Here, we observe a similar effect of GIPC MIR binding on single molecule tdwell (Figure 5E).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 83%
See 2 more Smart Citations
“…Hence, we propose that the release of myosin VI autoinhibition enhances motor flexibility and consequently the net flexibility of the motor-cargo linkage. In turn, the increased flexibility of the motor-cargo linkage has been previously shown to decrease the motor dwell time on the actin filament (tdwell) (32). Here, we observe a similar effect of GIPC MIR binding on single molecule tdwell (Figure 5E).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 83%
“…Artificially dimerized myosin VI ensembles patterned on DNA nanotubes yielded higher actin gliding velocities when the stiffness of the synthetic linkage between motor and nanostructure was decreased (17). Likewise, artificially dimerized myosin VI motors patterned on DNA origami scaffolds moved faster on single actin filaments when the cargo-motor linkage stiffness was reduced (32). While these studies demonstrated a biophysical mechanism to modulate cargo speed, its cellular relevance has not been established.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
See 1 more Smart Citation
“…Since legs constantly bind and unbind to the surface, imparting force each time they do so, the particle's macroscopic mobility depends on the microscopic details of its legs. For example, leg flexibility and bond lifetimes control the average mobility of the particle [19,23,24], and differences in both parameters can be harvested to detect infected cells [25][26][27] or prevent viral infections [28]. Leg density affects how DNA-coated colloids nucleate and grow into crystals [29,30] and governs the long-range alignment of crystals [31][32][33].…”
mentioning
confidence: 99%
“…The article by Sivaramakrishnan and colleagues describes how the stiffness of the linkage between cargo and mysosin affects anchoring to actin and the length of individual steps taken by the motor protein. 13 It has been known for more than a century that mechanical forces can modulate cellular form and shape. Integral membrane proteins, as well as peripheral membrane proteins that oligomerize at the cell membrane, can exert mechanical force that results in membrane curvature, and membrane curvature and packing in turn exert a force that can modulate the functioning of integral membrane proteins.…”
mentioning
confidence: 99%